Analisis Pelaksanaan Karakter Disiplin Siswa Kelas IV dalam Pembelajaran Daring - Fajrin Nida Amalia; Ari Widyaningrum; Qoriati Mushafanah (STKIP Andi Matappa Pangkep, 2022)
This study aims to determine and describe the implementation of the discipline character of fourth grade students in online learning at SD Negeri Tamansari 03, Tlogowungu District. This research method is qualitative research using data collection techniques in the form of questionnaires, interviews, observations, and documentation. Based on the findings of the research, it can be concluded that the problems in this study are due to changes in the pattern of education from being face-to-face at school to learning at home online. This indirectly restores the function of parents as the main foundation of character education for students, so it is very important the role of parents in accompanying children to study online at home so that appropriate disciplined characters are needed according to student needs. Of the 10 fourth grade students at SD Negeri Tamansari 03, Tlogowungu District, 6 students applied permissive discipline, 4 students applied democratic discipline, and fourth grade students did not apply authoritarian discipline. Based on the results of the research, suggestions that can be conveyed are that students are expected to be able to establish competent relationships with teachers such as being on time in collecting assignments, following from the beginning to the end of online learning by applying the right discipline according to student needs.